Staphylococcus aureus biofilm-associated component PNAG stimulates the secretion of the immunomodulatory chemokine CXCL10 via Dectin-1 signaling - Reza Gheitasi; Daniel Weiss; Mario M. Müller; Karolin Sommer; Daniela Röll; Alexander Mosig; Mathias. W. Pletz; Oliwia Makarewicz (Communications Biology)
Abstract Staphylococcus aureus is a common human pathogen associated with many infections. The key factor contributing to the virulence of S. aureus is its ability to form difficult-to-treat and recalcitrant biofilms. One of the major staphylococcal biofilms matrix compounds is poly-N-acetylglucosamine (PNAG). In previous study, we observed an increased secretion of various cytokines and chemokines when immune cells were stressed by S. aureus biofilms. In this study, we aimed to analyze the effect of PNAG on the secretion of the CXCL10 chemokine subfamily by peripheral blood mononuclear cells and monocytes and studied the connection to the Dectin-1-Syk-CARD9 signaling pathway, as Dectin-1 is the major pattern recognized by polysaccharide structures. We showed that, in contrast to the major virulence factor surface protein A, PNAG primarily elevates the secretion of CXCL10. This secretion was interrupted by blocking the Dectin-1 receptor or tyrosine kinase Syk. PNAG exposure resulted in increased Dectin-1 and CARD9 expression as well as increased NF-κB and CXCL10 expression, which may be related to the long-term memory processes of T cells. We also showed that PNAG induces the formation of CD14 + CXCL10+ monocytes that can migrate to the site of infection, triggering an innate immune response against S. aureus. This study provides insights into the complex interaction of the staphylococcal biofilms matrix with immune chemotaxis and shows that immunologic processes leading to bacterial infections should be viewed in a more differentiated manner, as biofilms are the preferred formation of microorganisms.